2013 Africon 2013
DOI: 10.1109/afrcon.2013.6757631
|View full text |Cite
|
Sign up to set email alerts
|

Smart metering implementation for enabling Water Conservation and water demand management: An investigation in Gauteng, South Africa

Abstract: Due to water scarcity and growth demand, the provision of water of good quality and quantity is essential to utilities in urban areas. Gauteng municipalities in South Africa obtain water from the Vaal River system. The water demand exceeds the supply there-of. Between 36 -40 % of the water is Non-Revenue Water (NRW) in the municipalities and is a source for great concern. A research study was conducted and it focused mainly on Water Conservation and Water Demand Management (WC/WDM) in municipalities. The aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…A brief review of the water-climate studies in the SADC showed that most water and climate studies in the region are conducted separately (Brewis et al 2019) with a few exceptions by Derrick Ngoran et al (2015), Kusangaya et al (2014) and Liehr et al (2017) that seek to address both water and climate jointly. South Africa has carried out most research on water-resource management than any other country in the SADC (Masia & Erasmus 2013;Mckenzie & Wegelin 2009), followed by the impact of climate change (Du Plessis 2017) and groundwater modelling (Abiye 2016). Studies conducted in Namibia (Angula 2010;Jury & Engert 1999;Kluge et al 2008;Liehr et al 2017;Mbaiwa 2004;Newsham & Thomas 2011) focus more on the prediction of the impact of climate and water scarcity because of the arid nature of the country.…”
Section: List Of Tablesmentioning
confidence: 99%
“…A brief review of the water-climate studies in the SADC showed that most water and climate studies in the region are conducted separately (Brewis et al 2019) with a few exceptions by Derrick Ngoran et al (2015), Kusangaya et al (2014) and Liehr et al (2017) that seek to address both water and climate jointly. South Africa has carried out most research on water-resource management than any other country in the SADC (Masia & Erasmus 2013;Mckenzie & Wegelin 2009), followed by the impact of climate change (Du Plessis 2017) and groundwater modelling (Abiye 2016). Studies conducted in Namibia (Angula 2010;Jury & Engert 1999;Kluge et al 2008;Liehr et al 2017;Mbaiwa 2004;Newsham & Thomas 2011) focus more on the prediction of the impact of climate and water scarcity because of the arid nature of the country.…”
Section: List Of Tablesmentioning
confidence: 99%
“…A brief review of the water-climate studies in the SADC showed that most water and climate studies in the region are conducted separately (Brewis et al 2019) with a few exceptions by Derrick Ngoran et al (2015), Kusangaya et al (2014) and Liehr et al (2017) that seek to address both water and climate jointly. South Africa has carried out most research on water-resource management than any other country in the SADC (Masia & Erasmus 2013;Mckenzie & Wegelin 2009), followed by the impact of climate change (Du Plessis 2017) and groundwater modelling (Abiye 2016). Studies conducted in Namibia (Angula 2010;Jury & Engert 1999;Kluge et al 2008;Liehr et al 2017;Mbaiwa 2004;Newsham & Thomas 2011) focus more on the prediction of the impact of climate and water scarcity because of the arid nature of the country.…”
Section: List Of Tablesmentioning
confidence: 99%
“…Some of the other applications along with their advantages of using smart metering can be better understand from Figure 7. Masia et al [94] have shown usage of a smart meter for reducing NRW losses and demand management in WDS of Gauteng, South Africa. Smart water metering has created awareness among the 40% of the population regarding excess water consumption by them.…”
Section: Smart Metering For Water Distribution Systemmentioning
confidence: 99%